The database of the Nikolaev Astronomical Observatory as a unit of an international virtual observatory - Protsyuk, Yu.; Pinigin, G.; Shulga, A. (Кинематика и физика небесных тел, 2005)
Results of the development and organization of the digital database of the Nikolaev Astronomical Observatory (NAO) are presented. At present, three telescopes are connected to the local area network of NAO. All the data obtained, and results of data processing are entered into the common database of NAO. The daily average volume of new astronomical information obtained from the CCD instruments ranges from 300MB up to 2GB, depending on the purposes and conditions of observations. The overwhelming majority of the data are stored in the FITS format. Development and further improvement of storage standards, procedures of data handling and data processing are being carried out. It is planned to create an astronomical web portal with the possibility to have interactive access to databases and telescopes. In the future, this resource may become a part of an international virtual observatory. There are the prototypes of search tools with the use of PHP and MySQL. Efforts for getting more links to the Internet are being made.